PENGARUH AMENITAS DAN AKSESIBILITAS TERHADAP KEPUASAN WISATAWAN PADA WISATA BAHARI PANTAI MELASTI BALI - Lenny Kurnia Octaviani (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2025)
This study aims to analyze the influence of amenities and accessibility on tourist satisfaction at Melasti Beach, Bali. Amenities and accessibility are considered essential factors affecting tourist experiences. A quantitative approach with a survey method was employed, with data collected through questionnaires from 100 respondents. Validity and reliability tests ensured the quality of the research instruments, while multiple linear regression analysis was used to assess the influence of these variables. The results show that both amenities and accessibility have a positive and significant impact on tourist satisfaction, accounting for 61.9% of the variation in tourist satisfaction, while the remaining 38.1% is influenced by other factors. These findings highlight the importance of improving facilities and access to Melasti Beach to enhance visitor satisfaction and provide insights for tourism managers in developing facilities and infrastructure at marine tourism destinations.